Bead-like Co-doped ZnO with improved microwave absorption properties. Issue 6 (15th April 2019) - Huang, Xiaogu; Zhang, Mingji; Qin, Yushuang; Chen, Yunyun
Abstract: Based on the superior semiconducting and dielectric properties of traditional ZnO microwave absorbers, we report a significant enhancement of microwave absorption performance using a bead-like Co doping technique with an optimized morphology, fewer functional defects and multiple electromagnetic loss mechanisms. The bead-like ZnO is prepared by electrospinning and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), vibrating sample magnetometer (VSM), X-ray photoelectron spectroscopy (XPS) and vector network analyzer (VNA). The results show that the phase composition of ZnO is not changed, but lattice shrinkage and defects are caused by the Co doping. The as-prepared Co-doped ZnO exhibits ferromagnetic properties and excellent electromagnetic loss performance. The dielectric loss is caused by interfacial polarization and dipole polarization. The magnetic loss is derived from magnetic hysteresis loss and residual loss. The optimal microwave absorption properties are obtained when the Co doping content is x = 0.09. The effective microwave absorption bandwidth with reflection loss less than − 10 dB can reach 11.6 GHz (6.4–18 GHz) at a coating thickness of 1.0–4.0 mm. This study demonstrates a promising method to improve the microwave absorption properties of ZnO.